Assessment of state of Dactylorhiza fuchsii (Orchidaceae) populations from the Altai mountains of Kazakhstan (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sumbembayev AA, Tergenbaeva ZHT, Kudabayeva GM, Tashmetova RS, Genievskaya YA, Szlachetko DL. 2022. Title. Biodiversitas 23: 4385-4399. The article presents the results of studying the current state of populations of a rare species - Dactylorhiza fuchsii in the Kazakhstan Altai. As a result of expeditionary studies, four main regions were identified, which were represented by 12 populations. Floristic plasticity according to the Jaccard coefficient (12-24%) showed a high heterogeneity of the studied populations. The cluster population dendrogram showed a clear dependence of the floristic composition of accompanying species on geographic location in terms of species similarity and difference of communities. External similarity was studied according to 10 morphometric features. The PCA analysis shows that the external structure is influenced by vertical zoning. Pearson's correlation analysis showed a stable direct and inverse dependence of morphometric characteristics on some environmental conditions (0.74-0.95). According to the data ANOVA disperse analysis, among studied environmental factors, soil nutrient richness (N) and humidity (F) had demonstrated the broadest significant effects (P-values from < 2e-16 to 0.001 for N and from 8.02e-09 to 0.02 for F) on plants morphology influencing eight out of ten morphological traits. Distribution regions of D. fuchsii have low vitality, and most populations are characterized as depressed. The results harmoniously complement the fundamental research on the state of D. fuchsii populations throughout the distribution range of the species.
Keywords: ecological optimum, floristic composition, metric characteristics, Red Data Book species